Czym się różni singiel od singielki? Płeć kulturowa jako element tożsamości singli - Sobolczyk, Anna (Kultura i Społeczeństwo, 2008)
Identity is an awareness of being the same “me” in the past, despite changes over time, as well as being close to similar social categories in the present. One of the most important for self-identiﬁcation categories of others are people of the same gender. Gender is a collection of roles recognised as being typical for representatives of a given sex, particular behaviour and personality traits. We describe them respectively as structural, symbolic and emotional dimensions of masculinity and femininity. The aim of the article is to provide an answer to the question of how gender affects the identity of singles – those who are neither parents or partners. Considered are independently: work, family, home and free time on the basis of information obtained from interviews and the European Social Survey. This leads to the conclusion that work and home are areas where sex has less impact on the life of a single than on that of other members of the society. Singles’ femininity and masculinity manifest themselves mainly symbolically during their free time. Typical for people living alone is that they consciously shape their behaviour as feminine, masculine or neutral.